ARYA PENANGSANG GUGUR: ANTARA HAK DAN PULUNG KRATON DEMAK BINTARA - Ahmad Nurhamid (Universitas Stikubank (UNISBANK) Semarang, 2009)
This paper explores in a historical perspective that ‘rights’ cannot be claimed without ‘pulung’ (something good falling upon anyone of God’s choice). Everyone knows that Arya Penangsang has the right to be the King of Demak with respect to heredity. However, it was Jaka Tingkir, only the son in law of the King managed to be crowned as then King of Demak. Arya Penangsang himself died in vain due to his greed for power. In terms of magical strength, Arya Penangsang was far ahead beyond anyone else since he was a beloved student of Sunan Kudus, a very respectable figure among Wali Sanga (9 holy men in Javanese Islam Founder). Yet, God knows. Good strategies and patience won the game. Key Words: heredity, magical strength, strategies